Studi Etnografi Virtual: Konstruksi Identitas Virtual Anggota Subkultur Humor Mencela Diri Di Tiktok - Widiastuti, Anindita; Bajari, Atwar; Mirawati, Ira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Islamic Business Law is a legal dimension in business activities that is based on Within the subculture of self-deprecating humor on TikTok, users are self-deprecating in the videos they upload or the comments they post on related videos. The self-deprecation that users do on TikTok encourages users to pay more attention to the virtual identity they want to show to other TikTok users. Therefore, this study aims to understand how TikTok users as members of the self-deprecating humor subculture construct their virtual identities on TikTok. In order to understand the members of a subculture and the culture exchanged between members of the subculture in depth, this qualitative research uses a virtual ethnography method to observe subcultures of self-deprecating humor on TikTok for six months. This research finds out how members of a subculture can construct their virtual identity through profile sections and through the language used in interactions with members of other subcultures. In general, members of subcultures construct their virtual identities with the aim of disguising their real identities. At the same time, members can construct virtual identities that can reflect on themselves. Over time, members of the subculture adapt the virtual identities they construct taking into account the language and culture that prevails within the subculture of self-deprecating humor on TikTok. The freedom of members of subcultures to self-deprecate is achieved because of the freedom of virtual identity formation allowed by TikTok.